Guilt and ginataan eaudiobook - Manansala, Mia P. (Tita Rosie's Kitchen Mystery, 2024)
Autumn is in full swing for the town of Shady Palms—the perfect time for warm drinks, cozy cardigans, and…dead bodies? The annual Shady Palms Corn Festival is one of the town’s biggest moneymakers, drawing crowds from all over the Midwest looking to partake in delicious treats, local crafts, and of course, the second largest corn maze in Illinois. Lila Macapagal and her Brew-ha Cafe crew, Adeena Awan and Elena Torres, are all too happy to participate in the event and even make a little wager on who can make it through the corn maze the fastest—but their fun is suddenly cut short when a dead body is found in the middle of the maze…and an unconscious Adeena lies next to it, clutching a bloody knife. The body is discovered to be a local politician’s wife, and all signs—murder weapon included—point to Adeena as the culprit. But Lila knows her best friend couldn’t have done this, so she and her crew put on their sleuthing caps yet again to find the killer who framed Adeena and show them what happens when they mess with a Brew-ha…